Pengaruh Terapi Aktivitas Kelompok (TAK) : Stimulus Persepsi Sesi 1-3 Terhadap Kemampuan Mengontrol Halusinasi Pendengaran Pada Pasien Skizofernia - Pratiwi Gasril; Yeni Yarnita; Putri Afrilliya; Yeni Devita (LPPM Universitas Muhammadiyah Riau, 2021)
Schizophrenia is a mental disorder characterized by abnormalities in the perception or expression of reality. One of the most common symptoms in schizophrenia is the appearance of hallucinations, which is about 70%. Purpose: This study is to effect Group Activity Therapy (TAK): Perception Stimulus sessions 1-3 on the Ability to Control Hearing Hallucinations in Schizophrenic Patients in Sebayang Room at Tampan Mental Hospital, Riau Province. This research research method is quantitative with a Quasi Experiment approach, conducted on 16 respondents from 03 to 13 March 2020 at the Tampan Mental Hospital, Riau Province. Researchers used the Auditory Hallucinations Rating Scale (AHRS) module and evaluation sheet before and after the intervention. The technique used univariate and bivariate analysis with Paired Sample T Test. The results showed a significant influence between Group Activity Therapy (TAK) Perceptual Stimulation of the Ability to Control Auditory Hallucinations, with a value of p = 0.01.